Late mortality and chronic health conditions in long-term survivors of early-adolescent and young adult cancers: a retrospective cohort analysis from the Childhood Cancer Survivor Study - Suh, Eugene; Stratton, Kayla L; Leisenring, Wendy M; Nathan, Paul C; Ford, Jennifer S; Freyer, David R; McNeer, Jennifer L; Stock, Wendy; Stovall, Marilyn; Krull, Kevin R; Sklar, Charles A; Neglia, Joseph P; et al. (The lancet oncology, 2020)
Treatment outcomes among survivors of cancer diagnosed during adolescence and early young adulthood have not been characterised independently of survivors of cancers diagnosed during childhood. We aimed to describe chronic health conditions and all-cause and cause-specific mortality among survivors of early-adolescent and young adult cancer. The Childhood Cancer Survivor Study (CCSS) is a retrospective cohort study with longitudinal follow-up of 5-year survivors diagnosed with cancer before the age of 21 years at 27 academic institutions in the USA and Canada between 1970 and 1999. We evaluated outcomes among survivors of early-adolescent and young adult cancer (aged 15–20 years at diagnosis) and survivors diagnosed at age younger than 15 years (matched on primary cancer diagnosis, including leukaemia, lymphoma, CNS tumours, neuroblastoma, Wilms tumour, soft-tissue sarcomas, and bone cancer) by comparing both groups to siblings of the same age. Mortality was ascertained with the National Death Index. Chronic health conditions were classified with the Common Terminology Criteria for Adverse Events. Standardised mortality ratios (SMRs) were estimated with age-specific, sex-specific, and calendar year-specific US rates. Cox proportional hazard models estimated hazard ratios (HRs) for chronic health conditions and 95% CIs. Among 5804 early-adolescent and young adult survivors (median age 42 years, IQR 34–50) the SMR compared to the general population for all-cause mortality was 5·9 (95% CI 5·5–6·2) and among 5804 childhood cancer survivors (median age 34 years; 27–42), it was 6·2 (5·8–6·6). Early-adolescent and young adult survivors had lower SMRs for death from health-related causes (ie, conditions that exclude recurrence or progression of the primary cancer and external causes, but include the late effects of cancer therapy) than did childhood cancer survivors (SMR 4·8 [95% CI 4·4–5·1] vs 6·8 [6·2–7·4]), which was primarily evident more than 20 years after cancer diagnosis. Early-adolescent and young adult cancer survivors and childhood cancer survivors were both at greater risk of developing severe and disabling, life-threatening, or fatal (grade 3–5) health conditions than siblings of the same age (HR 4·2 [95% CI 3·7–4·8] for early adolescent and young adult cancer survivors and 5·6 [4·9–6·3] for childhood cancer survivors), and at increased risk of developing grade 3–5 cardiac (4·3 [3·5–5·4] and 5·6 [4·5–7·1]), endocrine (3·9 [2·9–5·1] and 6·4 [5·1–8·0]), and musculoskeletal conditions (6·5 [3·9–11·1] and 8·0 [4·6–14·0]) when compared with siblings of the same age, although all these risks were lower for early-adolescent and young adult survivors than for childhood cancer survivors. Early-adolescent and young adult cancer survivors had higher risks of mortality and severe and life threatening chronic health conditions than the general population. However, early-adolescent and young adult cancer survivors had lower non-recurrent, health-related SMRs and relative risks of developing grade 3–5 chronic health conditions than childhood cancer survivors, by comparison with siblings of the same age, which were most notable more than 20 years after their original cancer. These results highlight the need for long-term screening of both childhood and early-adolescent and young adult cancer survivors. National Cancer Institute and American Lebanese-Syrian Associated Charities.